Current knowledge on alleviating Helicobacter pylori infections through the use of some commonly known natural products: bench to bedside - Malliga Raman Murali; Sangeetha Vasudevaraj Naveen; Chang Gue Son; Hanumantha Rao Balaji Raghavendran (Integrative Medicine Research)
Helicobacter pylori, a spiral-shaped Gram-negative bacterium, has been classified as a class I carcinogen by the World Health Organization and recognized as the causative agent for peptic ulcers, duodenal ulcer, gastritis, mucosa-associated lymphoid tissue lymphomas, and gastric cancer. Owing to their alarming rate of drug resistance, eradication of H. pylori remains a global challenge. Triple therapy consisting of a proton pump inhibitor, clarithromycin, and either amoxicillin or metronidazole, is generally the recommended standard for the treatment of H. pylori infection. Complementary and alternative medicines have a long history in the treatment of gastrointestinal ailments and various compounds has been tested for anti-H. pylori activity both in vitro and in vivo; however, their successful use in human clinical trials is sporadic. Hence, the aim of this review is to analyze the role of some well-known natural products that have been tested in clinical trials in preventing, altering, or treating H. pylori infections. Whereas some in vitro and in vivo studies in the literature have demonstrated the successful use of a few potential natural products for the treatment of H. pylori-related infections, others indicate a need to consider natural products, with or without triple therapy, as a useful alternative in treating H. pylori-related infections. Thus, the reported mechanisms include killing of H. pylori urease inhibition, induction of bacterial cell damage, and immunomodulatory effect on the host immune system. Furthermore, both in vitro and in vivo studies have demonstrated the successful use of some potential natural products for the treatment of H. pylori-related infections. Nevertheless, the routine prescription of potential complementary and alternative medicines continues to be restrained, and evidence on the safety and efficacy of the active compounds remains a subject of ongoing debate.